Implantación de la contabilidad comercial en Yesmar boutique, del cantón Catamayo, periodo julio – septiembre 2014 - Herrera Jiménez, Enid Guillermina (2015)
This thesis entitled Research: "IMPLANTATION OF BUSINESS ACCOUNTING YESMAR BOUTIQUE, THE CANTON CATAMAYO, PERIOD JULY - SEPTEMBER 2014" was performed for the purpose of developing the practical application of accounting system according to the needs of the company, whose business lacks an adequate accounting system, an initial inventory control where property rights and obligations of the company are controlled efficiently, considering the Generally Accepted Accounting Principles. Also it is disclosed to the owner of this business the result obtained by the Financial Statements. Note that this work was developed in accordance with the Rules of Academic System of the National University of Loja. The objectives in the company YESMAR BOUTIQUE, is reached satisfactorily, the application of accounting Perpetual Inventory System allowed to know the stock of merchandise and obtain reasonable Financial Statements; also through the organization of the documentation was structured Plan and User Accounts; was able to develop the accounting process to finally make accounting entries to generate timely and efficient financial statements. After the execution of fieldwork in the company profit was determined, the result was reflected in the preparation of financial statements that enable its owner to make sound decisions when the need arises; therefore it is recommended to continue applying Accounting by Perpetual Inventory System as it will help in the normal development of the activities of YESMAR BOUTIQUE